De cozinheiro a gastrônomo: um olhar para formação do professor de gastronomia - Toledo, Rosana Fernandez Medina (2010)
This study explains the situation on the training of teachers working in the college of technology in gastronomy. To so, this study demands to investigate the knowledge that teachers mobilize to form as gastronome and how the gastronomy's teachers have had access to this knowledge. For the development of research, it sought theoretical references for authors who research the development of gastronomy as Flandrin (1998), Montanari (1998), Franco (2001) and Leal (1998), authors who investigating the training of teachers as Tardif (2002), Furlanetto (2003), Freire (2000), Gomez (1992), Nóvoa (1995) and Schön (1995) and in studies of Analytical Psychology developed by Jung (1964). The research was conducted with teachers working in higher educational institutions of gastronomy in higher education institutions in the city of Sao Paulo. To so it sought teachers with academic teaching or not and was analyzed important points in their educational performance. What led them to teaching. The discussion revolves around a quest to answer the following problem: The professor of gastronomy must have academic teaching or not, just to practice and be appointed from the labor market? The teachers were interviewed and reported their stories of life and what led them to the path of teaching, its theoretical and methodological approaches to pursue the teaching profession. It should continually review the teacher's role in contemporary education, which means considering the speed, the construction and deconstruction of the changes underway. Today the technology courses already occupy a large part of higher education in Brazil. We are acting as teaching professionals with specific training and experience in the labor market in their methodological foundations is laid in instrumental conception.